Atmospheric Contributors to Heavy Rainfall Events in the Arkansas-Red River Basin - Taylor A. McCorkle; Skylar S. Williams; Timothy A. Pfeiffer; Jeffrey B. Basara (Advances in Meteorology)
This study analyzed the top 1% 24-hour rainfall events from 1994 to 2013 at eight climatological sites that represent the east to west precipitation gradient across the Arkansas-Red River Basin in North America. A total of 131 cases were identified and subsequently classified on the synoptic-scale, mesoscale, and local-scale to compile a climatological analysis of these extreme, heavy rainfall events based on atmospheric forcings. For each location, the prominent midtropospheric pattern, mesoscale feature, and predetermined thermodynamic variables were used to classify each 1% rainfall event. Individual events were then compared with other cases throughout the basin. The most profound results were that the magnitudes of the thermodynamic variables such as convective available potential energy and precipitable water values were poor predictors of the amount of rainfall produced in these extreme events. Further, the mesoscale forcings had more of an impact during the warm season and for the westernmost locations, whereas synoptic forcings were extremely prevalent during the cold season at the easternmost locations in the basin. The implications of this research are aimed at improving the forecasting of heavy precipitation at individual weather forecasts offices within the basin through the identified patterns at various scales.